Ne eat iudex ultra petita partium od prawa rzymskiego do czasów współczesnych. Uwagi na tle polskiego procesu cywilnego - Laskowska-Hulisz, Agnieszka (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The principle ne eat iudex ultra petita partium, that is let the judge does not go beyond the demands of the parties is nowadays recognized as a prohibition of judicial over the demand. This principle is not literally confirmed in the texts of Roman law. It comes from later studies referring to this law. In modern law, this sentence is an expression of one of the basic and at the same time the most important rules of adjudication and the guarantee of the implementation of the principle of availability in the civil process. The rule is the right to initiate a civil trial and to determine the limits of the legal protection sought are vested in the legitimate entity. In turn, it is expressed in the fact that the court is not allowed to initiate the trial without the party’s claim it is not allowed to decide on the object that was not covered by the request or award more than the request. In order to discuss the title issue in the paper, the genesis of that principle and then the historical and legal evolution of the Polish legal regulations related to this principle was briefly presented in the paper, in order to present briefly the form which the Polish legislature gave in the Code of Civil Procedure.